The Impact of Urbanization on Energy Demand: An Empirical Evidence from Somalia - Warsame, Abdimalik Ali (International Journal of Energy Economics and Policy, 2022)
Somalia is recovering from a long-period of civil unrest and political instability. The urbanized population are growing at unprecedented growth rate which ultimately results in an increase in energy demand. To this end, this study assesses the effect of urbanization on energy demand in Somalia while controlling the effects of economic growth and population growth. To achieve the aim, the study employs fully modified ordinary least square (FMOLS), canonical cointegration regression (CCR) and impulse response function (IRF) with time series data spanning from 1990 to 2018. Before the long-run model estimation, the study utilizes Augmented Dickey-Fuller (ADF) and Philips’s Perron (PP) tests to check the unit root problem, and they demonstrate that all the variables are stationary at first difference I (1). Furthermore, the empirical results indicate that urbanization impedes energy consumption, whereas economic growth and population growth increase energy demand in the long-run. Besides, the result of IRF demonstrate that one standard deviation shock in urbanization (lnUB) results in energy consumption to decrease (lnEC) in the whole 10 periods. This calls for the Somali policy makers to consider urbanization as an effective determinant while targeting energy conservation policy in order to mitigate the fossil fuel energy use.